Bone remodeling in sigmoid sinus diverticulum after stenting for transverse sinus stenosis in pulsatile tinnitus: A case report - Qiu, Xiao-Yu (World J Clin Cases, 2021)
BACKGROUND: Pulsatile tinnitus (PT) is a potentially disabling symptom that has received increasing attention. Multiple causes of PT have been confirmed by targeted treatment. However, dynamic changes of related structures in PT patients with multiple causes after stenting for ipsilateral transverse sinus stenosis (TSS) have not been previously reported. We report such a case and present postoperative computed tomography venography (CTV) follow-up findings to demonstrate the decreased sigmoid sinus diverticulum and bone remodeling. CASE SUMMARY: A 45-year-old man suffered from left-sided PT for 15 years that was occasionally accompanied by headache and dizziness. Pre-operative CTV revealed left-sided sigmoid sinus wall anomalies (SSWAs), TSS, outflow dominance, large posterior condylar emissary vein, and an empty sella turcica. A cerebrospinal fluid pressure of 270 mmH(2)O was further detected. The sound disappeared immediately after stenting for ipsilateral TSS, with no recurrence during 2 years of follow-up. After the procedure, the patient underwent four consecutive CTV examinations. The diverticulum decreased 6 mo after the procedure with new bone remodeling. The density of the remodeled bone was further increased 1 year later, and a hardened edge was formed 2 years later. CONCLUSION: PT associated with SSWAs, TSS, and idiopathic intracranial hypertension can be cured by stenting for TSS alone. And bone remodeling around SSWAs is a more significant finding.